2020
DOI: 10.1155/2020/6102940
|View full text |Cite
|
Sign up to set email alerts
|

Disaster Preparedness among Emergency Medical Service Providers: A Systematic Review Protocol

Abstract: Background. The emergency medical service (EMS) provides first-line medical care to people who require urgent medical care in emergency and disaster situations. Preparedness is the most effective approach for the management of disaster risks, and it is essential for the emergency medical service (EMS) providers, such as paramedics, emergency medical technicians (EMT), and other EMS personnel. This systematic review will explore evidence on the preparedness of emergency medical service providers in emergency an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 8 publications
0
23
0
Order By: Relevance
“…When managing a CBRNe situation, four phases will have to be dealt with: threat, preparedness, response and remediation [3]. A key part in being able to deal with such situations effectively is the training of all actors involved, such as first responders, law enforcement agencies, paramedics, or the military [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When managing a CBRNe situation, four phases will have to be dealt with: threat, preparedness, response and remediation [3]. A key part in being able to deal with such situations effectively is the training of all actors involved, such as first responders, law enforcement agencies, paramedics, or the military [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, actors from these different professions might feel more prepared or be more willing and ready to respond to CBRNe incidents if they receive specialized training. For example, a study with paramedics showed that those who recently (i.e., in the prior three years) received CBRNe training were more willing to respond to CBRNe, and that willingness was furthermore positively related to the quality of their training [4]. Willingness and feelings of readiness increased if the paramedic's training involved simulations and hands-on practices [4].…”
Section: Introductionmentioning
confidence: 99%
“…We must have the necessary response in facilities, decontamination, triage, teams and human resources in the hospital’s operational plan regarding COVID-19 disease (Majd et al , 2020). The World Health Organization’s guidelines on the management of the disease include: identifying reference hospitals (formulating how to refer, accept and coordinate), providing appropriate personal protective equipment by the Ministry of Health's notification protocol, isolation and quarantine of suspected cases and activation of the disease care team in the hospital surveillance system for the disease its distribution in hospitals, will be among the measures of the hospital's readiness in this area (Balduzzi et al , 2020). In comparison to our study, these indicators were only reported in domestic studies in disease management with 71% and risk analysis of hospital preparedness in Asefzadeh et al (2016) with a moderate level.…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 ] have evaluated the disaster preparedness of hospitals in their research areas. However, to our knowledge, except for a systematic review protocol that recently was published to assess the preparedness of EMS providers in emergencies and disasters,[ 19 ] there is no comprehensive study conducted on disaster preparedness of EMS systems through a global lens. This study will address this gap by doing a systematic review of the literature in this area.…”
Section: Discussionmentioning
confidence: 99%